Intra-industry trade, factor proportions and aggregation - John Somerset Chipman (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1986)
Some empirical extrapolations are performed which indicate that if the process of disaggregation were to be carried sufficiently far (to approximately the 17th to 23rd SITC level), virtually all intra-industry trade could be expected to disappear from international trade statistics. It is also shown under the assumption of Cobb-Douglas technology and preferences that the amount of intra-industry trade between countries is an increasing function of the closeness of the production functions in the aggregated industry. Finally, in a 3-country 3-commodity 3-factor model it is shown that there will be more trade between countries that are similar than between countries that are dissimilar in their factor endowments provided the commodities in which they have a comparative advantage have sufficiently similar production functions; this tendency is further accentuated if either (1) there is a high relative preference among world consumers for the products of the similar countries, or (2) the similar countries are large in comparison to the dissimilar one, or both.
Keywords: 330